Efficacy of albendazole, levamisole and ivermectin against gastro-intestinal nematodes in naturally infected goats at the National Semi-arid Resources Research Institute, Serere, Uganda - Byaruhanga, C.; Okwee-Acaib, J. (Veterinary Parasitology, 2013)
A study was conducted between April and July, 2011 to determine and compare the efficacy of albendazole (ABZ), levamisole (LVM) and ivermectin (IVM) against gastrointestinal nematodes in naturally infected Mubende and Boer crossbred goats at the National Semi-arid Resources Research Institute in Serere, Uganda. Forty Mubende goats and 31 Boer crosses were each blocked by age and sex and randomly assigned to four groups. The first group of each breed served as the untreated control, the second was treated with albendazole (5 mg/kg BW), the third with levamisole hydrochloride and oxyclozanide (7.5 and 15 mg/kg BW) and the fourth with ivermectin (0.2 mg/kg BW). Each group included 7–11 animals. Treatments were administered with doses of goats in albendazole and ivermectin, and doses of sheep in levamisole, as recommended by the manufacturers. In the treated groups, goats received anthelmintics basing on individual weights. Fecal egg counts, expressed as eggs per gram and larval cultures were done on day zero before treatment and on day 13 after anthelmintic treatment. Efficacy for each anthelmintic was determined by the Fecal Egg Count Reduction Test (FECRT). In Mubende goats, ABZ, LVM, and IVM reduced FEC by 28.5%, 91%, and 98%, respectively. In Boer crosses, ABZ, LVM, and IVM reduced FEC by 11%, 84.88% and 78.47%, respectively. At a 95% CI, only IVM was more effective in Mubende goats than Boer crosses (t = 2.564, p < 0.05). This may indicate occurrence of anthelmintic resistance in the goat farming sector in Uganda. Further studies need to be done to clarify the state of efficacy of the commonly used anthelmintics covering different agro ecological zones and species of animals in Uganda.